Physical Exercise Promotes a Reduction in Cardiac Fibrosis in the Chronic Indeterminate Form of Experimental Chagas Disease - Pedra-Rezende, Yasmin; Barbosa, Juliana M. C.; Bombaça, Ana Cristina S.; Dantas-Pereira, Luiza; Gibaldi, Daniel; Vilar-Pereira, Glaucia; dos Santos, Hílton Antônio Mata; Ramos, Isalira Peroba; Silva-Gomes, Natália Lins; Moreira, Otacilio C.; Lannes-Vieira, Joseli; Menna-Barreto, Rubem F. S. (Frontiers in Immunology, 2021)
Chagas disease (CD), caused by the protozoan Trypanosoma cruzi, is a neglected tropical disease and a health problem in Latin America. The etiological treatment has limited effectiveness in chronic CD, thus new therapeutic strategies are required. Practice of physical exercises has been widely advocated to improve the quality of life of CD patients. The most frequent clinical manifestation is the chronic indeterminate form (CIF), and the effect of physical exercises on disease progression remains unknown. Herein, in a CIF model we aimed to evaluate the effect of physical exercises on cardiac histological, parasitological, immunological, mitochondrial and oxidative metabolisms, electro- and echocardiographic profiles. To establish a CIF model, BALB/c and C57BL/6 mice were infected with 100 and 500 Y strain trypomastigotes. At 120 days post infection (dpi), all mice groups showed normal PR and corrected QT intervals, and QRS complex. Compared with BALB/c mice, C57BL/6 mice showed lower parasitemia peak, mortality rate, and less intense myocarditis. Thus, C57BL/6 mice infected with 500 parasites were used for the subsequent analysis. At 120 dpi, decrease in cardiac mitochondrial oxygen consumption, and increase in reactive oxygen species (ROS) were detected. Increase in the number of analyzed mice, at 120 and 150 dpi, reduced heart rate and slight prolonged corrected QT interval were detected, which were then normalized at 180 dpi, thus characterizing the CIF. So, Y-infected mice were submitted to an exercise program on a treadmill for 4 weeks (from 150 to 180 dpi), five times per week in a 30-60 min daily training session. At 180 dpi, no alterations were detected in cardiac mitochondrial and oxidative metabolism, which were not affected by physical exercises, although ROS production increased. At 120 and 180 dpi, comparing infected and non-infected mice, no differences were observed in levels of serum cytokine, supporting that a crucial biomarker of systemic inflammatory profile was absent and not affected by exercises. Compared with sedentary mice, trained Y-infected mice showed similar parasite load and inflammatory foci but reduced cardiac fibrosis. Therefore, our data support that physical exercises promote beneficial changes that may improve the quality of life and prevent CD progression.